2007
DOI: 10.1111/j.1399-3046.2007.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of carotid arterial wall structure in pediatric renal transplants with ambulatory normotension and in treated hypertensive recipients*

Abstract: Increased carotid IMT was found to be associated with cardiovascular risk factors. As pediatric renal transplants are at high risk for cardiovascular disease, we examined whether there is a relationship between BP and IMT in normotensive and in treated hypertensive recipients after transplantation. Thirty-one recipients aged 10 +/- 3.5 yr (16 M, 15 F) underwent repeated carotid ultrasound examinations 5.4 +/- 3.2 yr after transplantation with a 4.1 +/- 1 yr interval and were followed with annual ambulatory BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
(85 reference statements)
2
24
0
Order By: Relevance
“…Thus, APWV and AI might remain elevated in the period post-RT. However, it is possible that decrease in arterial stiffness markers occurs later post-transplant as suggested by others [36][37][38]. In our study we found a correlation between APWV, AI, and graft function 6 months after RT.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, APWV and AI might remain elevated in the period post-RT. However, it is possible that decrease in arterial stiffness markers occurs later post-transplant as suggested by others [36][37][38]. In our study we found a correlation between APWV, AI, and graft function 6 months after RT.…”
Section: Discussionsupporting
confidence: 71%
“…The only significant predictor of carotid IMT after Rtx was systolic blood pressure. In another prospective study of 31 children after Rtx, it was found that CCA-IMT did not change in children after mean of 4 years after Rtx despite good blood pressure control and relatively good graft function [107]. However, when interpreting this data, it should kept in mind that CCA-IMT increases with age at a rate of 0.01-0.005 mm per year.…”
Section: Is Intima-media Thickening Reversible?mentioning
confidence: 81%
“…In contrast, Suwelack et al [27] showed high cIMT in a population of renal transplant patients with normal blood pressure during hemodialysis and after transplantation. Krmar and colleagues [28] believed that higher cIMT in pediatric renal transplantation was not related to BP but to the possibility of other influences. In our study there was no relationship between BP and cIMT.…”
Section: Discussionmentioning
confidence: 98%